Implementasi Penerapan Aplikasi E-Raport Menggunakan Metode RAD Pada SDN Rawa Badak Utara - Ricki Sastra; Mery Arjohan; Dicky Hariyanto; Arfhan Prasetyo; Numan Musyaffa (IMTechno: Journal of Industrial Management and Technology, 2023)
SDN Rawa Badak Utara 03 is one of the educational institutions under the guidance of the government and in 2019 SDN RBU 03 implemented the E-report application in accordance with the provisions called for by the government in rule number 23 of 2016 concerning educational assessment standards. However, in the implementation of the E-report application, there are several shortcomings that teachers complain about, such as the teacher being required to first record student grades in a blank format that is downloaded from the E-report and then enter the student's grades through the excel application and re-upload it so that this is make data collection time so quite time consuming. Based on these complaints, the authors would like to propose a solution to develop the development version of the E-report application to make it easier and more effective in managing student grade data. In the stage of developing the E-report version 2 application (the author's version) the author uses the RAD (Rappid Application Development) method because the method used in the development of additional software has a relatively short development cycle. RAD has 3 stages that are structured and interdependent at each stage, while the stages are as follows: (1) Planning requirements consisting of system requirements analysis, (2) RAD design workshop which is a stage where the design involves users, (3) Implementation which is the stage of the system that has been agreed upon, built and refined and then tested. With the E-report the author's version it makes teachers save more time by only entering grades once into the E-report application without having to download a blank format to input grades and make it easier for teachers to see the grades of students who do not reach the KKM or who do not. achieved.